Upaya Peningkatan Hasil Belajar IPA Melalui Metode Card Sort Kelas IV di MI Al Hidayah Rawa Denok Depok - Ernawati; Wasiatul Jannah; Helentina Mena; Zuhana; Daden Jamaludin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the improvement of science learning outcomes through the use of the Card Sort strategy in fourth-grade students of MI Al Hidayah Rawa denok Depok. The method used is Classroom Action Research (CAR) with a descriptive approach. The research subjects were 19 fourth - grade students. The study was conducted in two cycles. In the first cycle, 11 students (57.89%) achieved mastery learning. In the second cycle, the number increased to 18 students (94.73%). These results indicate that the Card Sort strategy is effective in improving science learning out comes in fourth-grade students at MI Al Hidayah Rawadenok, Pancoran Mas District, Depok City, West Java.